2013
DOI: 10.1371/journal.pone.0062171
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Twist and N-Cadherin Expression in NSCLC

Abstract: BackgroundMetastasis is the most common cause of disease failure and mortality for non-small cell lung cancer after surgical resection. Twist has been recently identified as a putative oncogene and a key regulator of carcinoma metastasis. N-cadherin is associated with a more aggressive behavior of cell lines and tumors. The aim of this study was to evaluate the clinical relevance of Twist and N-cadherin expression in NSCLC, and the effects of Twist1 knockdown on lung cancer cells.MethodsWe examined the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 36 publications
8
69
1
1
Order By: Relevance
“…This finding was not consistent with those of other studies, which showed that Twist1 depletion reduced ATC cell viability [20]. Data have shown that Twist1 depletion induces lung cancer cell apoptosis [31]. This suggested that PTC proliferation may be regulated by other factors.…”
Section: Discussioncontrasting
confidence: 68%
“…This finding was not consistent with those of other studies, which showed that Twist1 depletion reduced ATC cell viability [20]. Data have shown that Twist1 depletion induces lung cancer cell apoptosis [31]. This suggested that PTC proliferation may be regulated by other factors.…”
Section: Discussioncontrasting
confidence: 68%
“…Lymph node metastasis was evaluated in 21 studies with 3900 patients (positive lymph node metastasis versus negative lymph node metastasis) . Pooled RR indicated that increased N‐cadherin apt to cause lymph node metastasis (RR = 1.16, 95%CI [1.00, 1.35], I 2 = 57.6%, P = .806; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…IHC expression of VIMENTIN was also previously investigated in NSCLC, with 7%‐66% of overexpression depending on the IHC cutoff value . One study quantified CDH2 expression by RT‐qPCR in 30 NSCLC (stages I to IV) and found that 67% of tumors had N‐Cadherin overexpression, with a bad prognosis value . Four studies have found an association between VIMENTIN IHC overexpression and N+ status of NSCLC .…”
Section: Discussionmentioning
confidence: 99%